Antifertility effects of two Malaysian plants - Tan, C.H; Smadiyah, A (1983)
The effects of two indigenous plants on the fertility of rats have been studied. Lepidagathis longifolia, also known as Penluruh, Serga dan Penggugur, has been found to reduce the litter size of rats if an aqueous extract (500 and 550 mg/kg body weight) of its roots is administered orally for 10 days post-coitum. This finding is consistent with its alleged used as an abortifacient. In contrast, the oral administration of aqueous and ethanol extracts (250 mg/kg body weight; 30 days) of Hibiscus rosa sinensis flowers (Bunga raya) has no effect on the weight and histology of the sex organs of male rats.